Genetics, Biochemistry and Biophysical Analysis of Anthocyanin in Rice (Oryza sativa L.) - Yheni Dwiningsih; Jawaher Alkahtani (Universitas PGRI Semarang, 2022)
Rice (Oryza sativa L.) is the primary staple food for half of the world population. It is generally classified based on the grain color into black, red, purple, brown, green, and white. These colored rice are determined by the composition and concentration of anthocyanin pigments in different layers of aleurone, pericarp, and seed coat. Anthocyanins are also accumulated in various tissues of the rice plants, mostly in the grain, but are also presents in leaves, leaf sheath, floral organ, and hull. The type and concentration of the anthocyanins in rice tissues are influenced by the cultivars and developmental stages. Anthocyanin-enriched rice is related to the health effects, including antioxidant, antibacterial, and anti-inflammation activities that potentially use as functional food ingredients, dietary supplements, and natural colorants. Structural and regulatory genes are involved in anthocyanin biosynthesis of rice. Various molecular biology techniques have been applied to improve productivity, nutritional contents, and market value of pigmented rice. This review focused on the genetics, biochemistry and biophysical analysis of anthocyanin in rice that will facilitate rice breeding program to develop new high-yield pigmented rice varieties.